Eksplorasi Strategi Presenter dalam Memicu Transaksi di Live Shopping Tik Tok - Setiawan I.S, Teguh; Damayanti, Ratih; Setyobudi, Ciptono (KOMUNIKA, 2025)
Live shopping is an innovative form of digital marketing that combines real-time interaction with the convenience of online shopping. This study aims to explore the communication strategies used by presenters to trigger purchasing transactions on the TikTok Live Shopping platform. Using a qualitative approach and respondent perception analysis, the findings reveal that product knowledge, direct interaction, and delivery style significantly influence consumer buying interest. Presenters who can convey information persuasively, create interactive engagement, and effectively utilize platform features have a greater potential to boost conversion rates. Facial expressions, body gestures, and vocal tone also serve as crucial nonverbal elements that affect emotional responses from viewers. Additionally, promotions, discounts, and detailed product presentations are the main attractions that draw audience attention during live sessions. TikTok, as an entertainment-based platform, allows for more expressive and personal communication strategies. Therefore, the success of live shopping on TikTok highly depends on the presenter’s ability to build dynamic two-way communication. This study concludes that presenter communication strategies are central to creating an effective digital shopping experience. The findings contribute significantly to the development of live streaming-based marketing strategies in the digital economy era.